1997
DOI: 10.1002/(sici)1096-8628(19971112)72:4<455::aid-ajmg16>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Velocardiofacial manifestations and microdeletions in schizophrenic inpatients

Abstract: Velocardiofacial syndrome (VCFS) is associated with an increased frequency of schizophrenia and other types of psychiatric morbidity. In this study, we tried to identify a subgroup of schizophrenic patients with deletions in the VCFS region of the long arm of chromosome 22. For that purpose, we screened the records of two major general hospitals for patients with abnormalities characteristic of VCFS, such as cardiac anomalies and cleft palate, and cross-checked the data with the register of psychiatric hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…75,76 From the practical perspective, clinicians should be vigilant for VCFS, especially when psychosis occurs in the presence of other features, suggestive of the syndrome such as dysmorphology, mild learning disability or a history of cleft palate or congenital heart disease. 74,77 However, from the perspective of the genetic researcher, the most pressing question is whether the high rate of psychosis in VCFS provides a shortcut to a gene within the deleted region that is involved in susceptibility to schizophrenia in cases without a deletion. Support for this hypothesis is provided by the fact that several linkage studies have reported evidence for a schizophrenia locus on 22q (see above), and the bin spanning 22q11 is one of the most significant regions to emerge from the meta-analysis by Lewis et al 60 Finally, mice that are heterozygously deleted for orthologues of a subset of the genes that are deleted in VCFS have cardiovascular abnormalities similar to those observed in VCFS.…”
Section: Cytogenetic Abnormalities Associated With Schizophreniamentioning
confidence: 99%
“…75,76 From the practical perspective, clinicians should be vigilant for VCFS, especially when psychosis occurs in the presence of other features, suggestive of the syndrome such as dysmorphology, mild learning disability or a history of cleft palate or congenital heart disease. 74,77 However, from the perspective of the genetic researcher, the most pressing question is whether the high rate of psychosis in VCFS provides a shortcut to a gene within the deleted region that is involved in susceptibility to schizophrenia in cases without a deletion. Support for this hypothesis is provided by the fact that several linkage studies have reported evidence for a schizophrenia locus on 22q (see above), and the bin spanning 22q11 is one of the most significant regions to emerge from the meta-analysis by Lewis et al 60 Finally, mice that are heterozygously deleted for orthologues of a subset of the genes that are deleted in VCFS have cardiovascular abnormalities similar to those observed in VCFS.…”
Section: Cytogenetic Abnormalities Associated With Schizophreniamentioning
confidence: 99%
“…Several groups (Bassett et al 1998;Gothelf et al 1997;Murphy et al 1998) have shown that 22qDS may be identified in clinical populations with schizophrenia who are screened for the presence of common syndromal features (see Table 1 for proposed clinical screening criteria). Age at onset, psychotic symptoms, and comorbid symptoms are consistent with those usually found in schizophrenia (Bassett et al 1998;Gothelf et al 1997;Pulver et al 1994).…”
Section: Identifying 22qds In Schizophreniamentioning
confidence: 99%
“…These deletions or duplications of chromosomal regions often span multiple genes and can either increase risk or protect from diagnosis, presumably by altering the 'dosing' of the genes contained within the variant region (Grozeva et al, 2010;International Schizophrenia C, 2008;Stefansson et al, 2008). For example, 22q11 hemideletion is associated with high rates of schizophrenia (Gothelf et al, 1997;Karayiorgou et al, 2010;Murphy et al, 1999), whereas 22q11 duplication may protect against schizophrenia diagnosis (Rees et al, 2014), suggesting that expression levels of specific genes are critical to normal and pathological brain development.…”
Section: Introductionmentioning
confidence: 99%